Testing a Theoretical Model Predicting Uncertainty and Depression in Patients Undergoing Renal Replacement Therapy in Korea - Heeyoung Lee, PhD, APRN; Karen G. Schepp, PhD, APRN, FAAN; Youngmi Jung, PhD, RN (Elsevier, 2008)
The purpose of this study was to test hypothesized relationships among experiences of uncertainty, depression, and social support in a sample of subjects undergoing renal replacement therapy in Korea. Methods: Path analysis was used in the sample to examine the relationships among depression and experiences of uncertainty, direct social support, indirect social support, and demographic variables. The size of the sample was 104 patients. Patients received either hemodialysis at one of three clinics or continuous ambulatory peritoneal dialysis. Results: One hundred and four subjects participated in the study. It was found that 6.2% of variance in uncertainty was predicted by direct social support (β =− .267), and 46.2% of variance in depression was predicted by three variables: direct social support (β =− .517), economic status (β = .299), and number of admissions (β = .275). Unlike the theoretical model, experiences of uncertainty could not predict depression. Conclusion: The effectiveness of social support in relieving experiences of uncertainty and consequently depression was shown in this study. Moreover, depression in this population could be predicted by direct social support, economic status, and frequency of admission. The study was needed to investigate the relationship between depression and experiences of uncertainty with time covariates, as well as to find the factors that influence depression in patients with chronic renal failure.